Modified metacognitive therapy for anorexia nervosa: An open trial in an outpatient setting. Issue 7 (30th May 2022) - Lawson, Rachel; Carter, Janet D.; Britt, Eileen; Knowles, Karen; Then, Rebecca; Vallance, Joanna; Jenkins, Louise; Tauamiti, Rachel
Abstract: Objective: Current evidence indicates treatment for adults with anorexia nervosa (AN) requires improvement given recovery rates are low to moderate, and relapse rates are high. Metacognitive therapy (MCT) is an effective treatment for anxiety and depressive disorders. This study evaluates if MCT can be successfully modified to treat AN in a naturalistic clinical setting. Method: Twenty‐four patients with AN participated in an open trial of modified metacognitive therapy (MCT‐AN). Twelve of the 24 patients (50%) completed treatment. MCT was modified to include components specific to eating disorders. The MCT‐AN was delivered by clinical psychologists who had undertaken training in MCT in a specialist outpatient service. Group and single participant data analyses were undertaken on those who completed treatment. Results: As well as statistically significant differences from pre‐ to posttreatment in the group data there were also clinically significant improvements at the individual patient level for eating disorder and depressive symptoms, as well as weight. The mean number of therapy sessions was 18. Discussion: These findings indicate that MCT‐AN may be a promising intervention in the treatment of AN, warranting further investigation. Public Significance: Treatment for anorexia nervosa in adults requires improvement. Research indicates that Metacognitive therapy (MCT) is an effective treatment for anxiety and depression and may be applicable to the eating disorders. This small open trial suggests that MCT can be modified successfully to treat patients with anorexia nervosa (AN). The results are preliminary and require further research to provide more evidence on the effectiveness of this treatment for AN.